Abnormalities of Endocrine Function Tests in COVID-19-Recovered Individuals - Phibakordor L. Nonglait; Srivenkata Madhu; Nishant Raizada; Amitesh Aggarwal; Rafat Ahmed; Mohammad Aslam (Indian Journal of Endocrinology and Metabolism, 2025)
Introduction: Impact of COVID-19 on endocrine system due to the widespread distribution of Angiotensin Converting Enzyme-2 (ACE2) receptors in different endocrine organs of the body has been shown in several studies. However, most of these studies were in the setting of acute COVID-19. The present study was planned to comprehensively evaluate endocrine abnormalities in COVID-19-recovered individuals. Methods: Eighty-three COVID-19-recovered individuals were recruited 8-20 weeks following the recovery. They were further stratified according to disease severity as defined by the Indian Council of Medical Research (ICMR). After recording their demographic and clinical details, an evaluation of inflammatory markers and different hypothalamic-pituitary axes involving thyroid, adrenal, gonadal and prolactin axes was carried out in them. Those who were on treatment for a previous endocrine disorder were not included in the study. Results: Eighty-three patients [33 (39.7%): mild and 50 (60.3%): moderate to severe COVID-19] were recruited after a period of 14.7 ± 3.4 weeks after recovery. Forty-four patients (53%) had some form of endocrine dysfunction. Central pituitary axis dysfunction was observed in 28 patients (33.7%), of which alterations in prolactin (20.4%) were the most common. Thyroid function abnormalities were noted in 25 (30.1%) patients, while gonadal dysfunction was detected in 14% of males and 6% of reproductive-aged females, respectively. Conclusion: Endocrine function test abnormalities were seen in a significant proportion of individuals even after a mean period of more than 3 months post-recovery from COVID-19. These have implications for the long-term endocrine and metabolic health of COVID-19-recovered individuals, besides alerting physicians to interpret endocrine function tests with caution after recovery from acute COVID-19 illness.